2002
DOI: 10.1097/00007890-200210270-00016
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasminogen activator inhibitor-1 genotype with avascular osteonecrosis in steroid-treated renal allograft recipients1

Abstract: Hypofibrinolysis conferred by the 4G/4G PAI-1 gene variant is a major predisposing factor for AVN in renal transplant patients. The risk is particularly high in obese subjects or patients with persistent hyperparathyroidism. A prospective intervention study of early anticoagulation after renal transplantation is needed to assess whether glucocorticoid-associated AVN can be prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 29 publications
2
42
1
3
Order By: Relevance
“…Genotyping of the TPA gene Alu-repeat (I/D polymorphism in intron 8 of the TPA gene were genotyped by a polymerase chain reaction (PCR) [16]. Synthetic oligonucleotides obtained from TIB MOLBIOL Syntheselabor (Berlin, Germany) were used.…”
Section: Biochemical Assaymentioning
confidence: 99%
“…Genotyping of the TPA gene Alu-repeat (I/D polymorphism in intron 8 of the TPA gene were genotyped by a polymerase chain reaction (PCR) [16]. Synthetic oligonucleotides obtained from TIB MOLBIOL Syntheselabor (Berlin, Germany) were used.…”
Section: Biochemical Assaymentioning
confidence: 99%
“…The majority of association studies relating to osteonecrosis have concentrated on gene polymorphisms affecting the coagulation and fibrinolytic systems [6]. However, the association between genetic predisposition and thrombotic tendency may differ between ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] However, the relationship of genetic polymorphism of plasminogen activator inhibitor (PAI)-1 4G/5G and post-renal transplant FHON was controversial. 3,5 Nitric oxide (NO) is a multifunctional biomolecule and serves as an important signal in physiologic processes including angiogenesis, thrombosis, and bone turnover, which are known to be related to the pathogenesis of osteonecrosis. 7 It was reported that the predominant isoform of nitric oxide synthases expressed in normal adult bone is endothelial nitric oxide synthase (eNOS).…”
Section: Introductionmentioning
confidence: 99%